(untitled) (International Conference on Education and Innovation, 2025)
In the era of digital transformation, the integration of artificial intelligence (AI) and blockchain technologies is one of the current scientific directions. While AI allows for deep data analysis, prediction, and automation, blockchain ensures data security, transparency, and reliability. This article analyzes the interaction between AI and blockchain, the need for integration, and synergistic results. The study uses an analytical approach and benchmarking methods to study practical examples from the fields of finance, healthcare, IoT, and cybersecurity. The results show that integration allows for reliable data storage, increased stability of AI models, enhanced protection against attacks such as data poisoning, and automated decision-making in smart contracts. At the same time, transaction speed, resource requirements, and legal and ethical issues were identified as important limitations of integration. The discussion section presents the prospects for strengthening security based on new consensus mechanisms, extended data management platforms, and post-quantum cryptography. In conclusion, it was noted that the integration of AI and blockchain will open up new opportunities for technological and economic development on a global scale.